Penyelesaian Sengketa Penguasaan Tanah Hak Guna Bangunan di Atas Tanah Hak Pengelolaan Lahan Pemerintah Daerah - Made Putri Laras Sapta Ananda; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
In order to carry out the development, the HPL holder may grant rights to land above the HPL such as the Hak Guna Bangunan (HGB). However, in practice there are often legal problems related to the granting of land rights over HPL, especially HPL requests for land that is already an asset of the Regional Government's wealth to be converted into commercial activities. Problem formulation 1) What is the status of land tenure with Building Use Rights (HGB) over the Land Management Rights (HPL) of the Regional Government?; 2) Legal remedies taken in resolving disputes between HGB managers and HPL managers?. This type of research is normative juridical. HPL is not a land right as the Right to Build (HGB) which is regulated in the Basic Agrarian Law. The rights of the HGB holder are very limited because the HGB was established on land that is not theirs. HGB on HPL land of the Regional Government may be transferred or transferred with written approval from the Regional Government. HPL is non-transferable and cannot be used as collateral for debt with encumbrances with Mortgage Rights (HT). In practice, even though they have received quite strong protection in the existing provisions, there can be disputes between creditors with HGB guarantees over HPL.